STORYLINE STRUCTURE OF THE PROPHET RASULULLAH MOHAMMED SAW MUSEUM GALLERY AL JABBAR MOSQUE BANDUNG - Nazhar, Ryanty Derwentyana; Bahroun , Praymoedya Alramadhan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2024)
The objective of this study is to expound on the storyline structure and flow concept within the Gallery of the Museum of Prophet Muhammad saw Al Jabbar Mosque. Utilizing a qualitative descriptive method, the research involves an analysis of narrative structure focusing on the exhibition at the Gallery of the Museum of Prophet Muhammad, which narrates the life history of Prophet Muhammad. The study examines the storyline flow approach employed in organizing and communicating messages and stories to visitors. Results indicate that the narrative flow structure used in the exhibition is linear in its overarching theme and stratified in its subtopics. The museum’s storyline flow is instrumental in providing visitors with a profound and memorable experience. These research findings are expected to contribute to the advancement of design strategies aimed at conveying messages using the storyline flow concept.